Evaluation and Management of Blepharoptosis - Cohen, Adam J.; Weinberg, David A.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Written by experts in the fields of oculofacial plastic surgery and neuro-ophthalmology, Evaluation and Management of Blepharoptosis is an up-to-date, practical guide to the treatment of adults and children with ptosis. This comprehensive reference covers all aspects of blepharoptosis in an organized fashion. The book begins with evaluation of the patient to determine if true ptosis or pseudoptosis exists. The various categories of blepharoptosis are thoroughly and succinctly reviewed, along with suggested approaches to clinical management. Detailed descriptions of the various surgical techniques are replete with pearls provided by leading ptosis surgeons, along with advice regarding perioperative anesthesia and analgesia. Every surgeon should know how to handle the various surgical complications and surgical failure. Nevertheless, familiarity with surgical techniques is not enough. One must learn to identify risk factors and red flags that suggest a modified or conservative approach, or perhaps that surgery may be unwise. When surgery is unwarranted or unsuccessful, then one may consider nonsurgical therapeutic strategies. Regardless of treatment, the physician-patient relationship and detailed discussion with the patient prior to surgery regarding potential risks, complications, and realistic expectations impact patient satisfaction immeasurably. All of these issues are discussed in detail in this invaluable resource for the clinician.
Part I. Introduction -- 1.Introduction -- 2.The History of Ptosis Surgery -- 3.Eyelid Anatomy and Physiology with Reference to Blepharoptosis -- Part II.Approach to the Ptosis Patient -- 4.Risk Factor Assessment Prior to Ptosis Surgery -- 5.Ptosis: Nailing the diagnosis, and considering the differential diagnosis -- 6.Preoperative Decision Making in Ptosis Surgery -- Part III.Ptosis Subtypes -- 7.Pseudoptosis -- 8.Congenital ptosis -- 9.Involutional ptosis -- 10.Myogenic ptosis -- 11.Myasthenia Gravis -- 12.Neurogenic Blepharoptosis -- 13.Traumatic Blepharoptosis -- 14.Anophthalmic Ptosis -- 15.Lash Ptosis -- Part IV.Treatment -- A.Nonsurgical Options -- 16.The Non-Surgical Treatment of Ptosis -- B.Surgical Treatment -- 17.External levator resection -- 18.Minimal Dissection, Small Incision Ptosis Correction -- 19.Müllers muscle-conjunctival resection (posterior approach) -- 20.Open sky Muller s muscle resection for the correction of blepharoptosis -- 21.The Fasanella Servat procedure for ptosis -- 22.Full-Thickness Eyelid Resection for Blepharoptosis Correction -- 23.Frontalis Suspension for the Correction of Blepharoptosis -- Part V.Other Considerations -- 24.In-Office Surgery, Anesthesia and Analgesia -- 25.Ethnic and Gender Considerations in Ptosis Surgery -- 26.Aesthetic Considerations for the Ptosis Surgeon -- 27.Challenging Ptosis Scenarios -- 28.Ptosis surgery: Comparing different surgical techniques -- 29.Ptosis Surgery Failure and Reoperation -- 30.Complications of Ptosis Repair: Prevention and Management -- 31.Commentary: Perspective of a risk manager 12 Steps of a Successful Surgical Encounter -- 32. Conclusion.
Keywords: Medicine; Dermatology; Ophthalmology; Surgery; Medicine & Public Health; Ophthalmology; Plastic Surgery; Surgery; Dermatology